2021
DOI: 10.1155/2021/5572181
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Correction of Adult Spinal Deformities Requires Restoration of Distal Lumbar Lordosis

Abstract: Purpose. The aim of this study is to analyze results according to postoperative pelvic incidence-lumbar lordosis (PI-LL) mismatch in the management of adult spine deformity (ASD) patients. Recently, it has been reported that in addition to lumbar lordosis amount, lordosis repartition between its proximal and distal parts was crucial. Methods. We enrolled 77 consecutive ASD patients who underwent posterior spinal fusion and deformity correction between 2015 and 2018. On preoperative and 1-year follow-up radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Similarly, in our study, we found an ALIF at L5-S1 to more effectively match the Roussouly shape, while also improving proportionality in GAP. Likewise, Yilgor et al , 31 as well as further follow-up studies, have shown the importance of restoring proper distribution of lordosis within the L4-S1 segment on both lumbopelvic realignment and mechanical complications 32 . A study investigating the location of PSO on the apex and distribution of LL highlighted the impact on lower versus upper PSOs on both apex and distribution, without significant effects on specific Roussouly shape 33 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, in our study, we found an ALIF at L5-S1 to more effectively match the Roussouly shape, while also improving proportionality in GAP. Likewise, Yilgor et al , 31 as well as further follow-up studies, have shown the importance of restoring proper distribution of lordosis within the L4-S1 segment on both lumbopelvic realignment and mechanical complications 32 . A study investigating the location of PSO on the apex and distribution of LL highlighted the impact on lower versus upper PSOs on both apex and distribution, without significant effects on specific Roussouly shape 33 .…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, Yilgor et al, 31 as well as further follow-up studies, have shown the importance of restoring proper distribution of lordosis within the L4-S1 segment on both lumbopelvic realignment and mechanical complications. 32 A study investigating the location of PSO on the apex and distribution of LL highlighted the impact on lower versus upper PSOs on both apex and distribution, without significant effects on specific Roussouly shape. 33 The results of our study communicate a similar message, demonstrating a PSO at L3 or L4 had the greatest improvement on PT and PI-LL, with no correlation overall to Roussouly shape.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a statistical difference in LDI among the Roussouly types, DLL in all types was approximately 30° to 40° [4]. Pesenti et al proposed that DLL should be preserved or restored around 36° to reduce the risk of PJF [17].…”
Section: Discussionmentioning
confidence: 99%
“…This understanding can guide osteotomy selection and the restoration of the proportionate balance between the PI–LL and distal/proximal LL. 32 , 33 While lumbar lordosis has been shown to decrease with age, there is disagreement about where that decrease occurs. Non-invasive biomechanical measurements of healthy volunteers performed by Dreischarf et al 34 demonstrated an age-related decrease in LL, but through the mid-lumbar spine proximal to the apex of lordosis.…”
Section: Discussionmentioning
confidence: 99%